Hubungan Tingkat Kadar Fluoride Pada Air Dengan Indeks Karies Masyarakat Desa Bugbug Kecamatan Karangasem - Ni Luh Made Rare Ayu Sawitri; Ni Kd Fiora Rena Pertiwi; Desak Putu Yuli Kurniati (School of Dentistry Faculty of Medicine Udayana University, 2022)
Introduction: Dental caries occurs due to the demineralization process from the interaction of microorganisms. The demineralization process can be inhibited by regular administration of fluoride to the teeth. Fluoride is important to increase remineralization which it can stimulates, repair, and protect dentinal enamel. This mechanisms can against acid to avoids dental caries. Fluoride levels in drinking water can affect fluorine intake received by individuals. Geographically, there are various of fluoride levels in drinking water sources. This affects the frequency of dental caries until fluorosis can occur. This study aims to determine the correlation between levels of fluoride consentration in drinking water sources (PDAM water, village piped water and well water) with caries index of the community of Bugbug Village, Karangasem District. Method: This study used an observational analytic design with a cross sectional approach. The location of PDAM water sampling, village piped water and well water is in one of the houses of the Bugbug Village and the location of dental caries examination in the respondent, namely in the Head Office of the Bugbug Village Karangasem Sub-District Karangasem Regency. The observation of dental conditions was carried out on 96 men of 26-65 years old. Result: Based on the results of the research, the level of fluoride in PDAM water is relatively low, village piped water and well water are classified as moderate. The respondent's average DMF-T index is 2.15 which is low in the caries level. The Chi-Square test results obtained a value of p=0.04 (p<0.05). Conclusion: The conclusions of this study, there is a significant correlation between levels of fluoride consentration based on water sources with the caries index. Latar Belakang: Karies gigi terjadi disebabkan oleh proses demineralisasi dari adanya interaksi mikroorganisme. Proses demineralisasi dapat dihambat dengan pemberian fluoride yang teratur pada gigi. Fluoride berperan penting dalam meningkatkan remineralisasi yang merangsang perbaikan serta dapat melindungi enamel dentin terhadap zat asam sehingga terhindar dari karies gigi. Kadar Fluoride dalam air minum dapat mempengaruhi intake fluor yang diterima oleh individu. Secara geografis, kadar fluoride pada sumber air minum berbeda-beda. Hal ini mempengaruhi frekuensi karies gigi hingga dapat terjadi fluorosis. Penelitian ini bertujuan untuk mengetahui hubungan tingkat kadar fluoride dalam sumber air minum yaitu air PDAM, air perpipaan desa dan air sumur dengan indeks karies masyarakat Desa Bugbug Kecamatan Karangasem. Metode: Penelitian ini menggunakan desain analitik observasional dengan pendekatan cross sectional. Lokasi pengambilan sampel air PDAM, air perpipaan desa dan air sumur yaitu disalah satu rumah warga Desa Bugbug serta lokasi pemeriksaan karies gigi pada responden yaitu di Kantor kepala Desa Bugbug Kecamatan Karangasem Kabupaten Karangasem. Oberservasi kondisi gigi dilakukan pada 96 kepala keluarga berjenis kelamin pria dengan rentan usia 26-65 tahun. Hasil: Berdasarkan hasil penelitian tingkat kadar fluoride pada air PDAM tergolong rendah, air perpipaan desa dan air sumur tergolong sedang. Rata – rata indeks DMF-T responden adalah 2,15 yang tergolong tingkat karies rendah. Hasil uji Chi-Square diperoleh nilai p=0,04 (p<0,05). Conclusion: ada hubungan yang signifikan antara tingkat kadar fluoride berdasarkan sumber air dengan indeks karies.